2017
DOI: 10.1177/1078345817700802
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome Prevalence and Reduction in Inmates Prescribed Antipsychotic Medications

Abstract: The principal aim of this study was to establish whether a metabolic monitoring program implemented for second-generation antipsychotic medications (SGAs) was associated with any reduction in the prevalence of metabolic syndrome in adult inmates treated with antipsychotic medications in the New Jersey Department of Corrections. The average prevalence of metabolic syndrome in those prescribed SGAs decreased from 17.9% during the years before metabolic monitoring to 14.3% during the years of monitoring. The numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
1
3
0
1
Order By: Relevance
“…We could not determine the prevalence of metabolic syndrome because some of the analyses were not available (such as the values of LDL, HDL and blood pressure, which were not included in routine monitoring), but still, it is evident that, possibly due to low doses prescribed, a more physically active lifestyle, or both, the prevalence of obesity, hyperglycemia and hypercholesterolemia was almost nonexistent. This is in accordance with the findings of Reeves et al (2017). However, in this study, we noted that there is a lack of metabolic monitoring in prison settings that, despite mostly normal values of metabolic parameters among inmates, should be implemented.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…We could not determine the prevalence of metabolic syndrome because some of the analyses were not available (such as the values of LDL, HDL and blood pressure, which were not included in routine monitoring), but still, it is evident that, possibly due to low doses prescribed, a more physically active lifestyle, or both, the prevalence of obesity, hyperglycemia and hypercholesterolemia was almost nonexistent. This is in accordance with the findings of Reeves et al (2017). However, in this study, we noted that there is a lack of metabolic monitoring in prison settings that, despite mostly normal values of metabolic parameters among inmates, should be implemented.…”
Section: Resultssupporting
confidence: 92%
“…The use of psychotropic medications in incarcerated persons is beneficial in terms of symptoms reduction, prevention of relapse, suicide and violent outbursts. However, the use of those drugs, antipsychotics in particular, is commonly accompanied with adverse effects, some of which may significantly affect the quality of life and even increase the risk of serious metabolic and cardiovascular complications and death (Divac et al , 2014; Muench and Hamer, 2010; Reeves et al , 2017). Clozapine, as the most effective antipsychotic for aggressive and violent behavior could be very useful in forensic population, but is avoided due to adverse effects and the need for regular white blood cells (WBC) count monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…Por todas estas razones, se hace necesaria la implementación de sistemas de monitorización de todos los pacientes en tratamiento con antipsicóticos atípicos, ajustando bien la dosificación, evitando el uso de combinaciones múltiples de estos, controlando el peso, el índice de masa corporal, el perímetro abdominal, la presión arterial, los niveles de prolactina y realizando un electrocardiograma 26 . También se ha llevado a cabo este tipo de monitorización en pacientes penitenciarios, consiguiendo una disminución en la prevalencia del síndrome metabólico, así como una disminución en las prescripciones de neurolépticos con el transcurso del tiempo 27 .…”
Section: Discussionunclassified
“…For all these reasons, monitoring systems need to be implemented for all patients undergoing treatment with atypical antipsychotics, with adequate adjustments to dosage, avoiding the use of multiple combinations of antipsychotics, checking weight, BMI, abdominal circumference, blood pressure, prolactin levels and ECG tests 26 . This type of monitoring has been carried out on prison patients, and has brought about a decrease in the prevalence of metabolic syndrome, along with a drop in the number of prescriptions for neuroleptic drugs over time 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the monitoring of patients on AP, low levels of metabolic screening have also been shown in other populations, e.g., a recent random retrospective review of 100 charts from Australia showed that none of the patients on AP were monitored every 3 months as recommended, and such monitoring decreased over one year (Ward et al 2018). On the other hand, studies have shown that regular monitoring of patients maintained on SGA can significantly reduce the prevalence of MetS and the use of AP in general (Phillips et al 2015;Reeves et al 2017). Thus, closer clinical monitoring and administrative auditing are needed to improve the health outcomes of patients on AP in Qatar.…”
Section: Discussionmentioning
confidence: 99%